Physiological and molecular insights into adaptive responses of Vigna marina to drought stress - Liu, Yiming; Wang, Zhibo; Liu, Guodao; Shen, Wenhao; Lohani, Neeta; Wang, Peng; Ye, Xiuxu; Atieno, Mary; Dao Thi, Hang; Nghia, Nguyen Khoi; Hu, An; Yan, Linling; et al. (2025)
Drought is one of the most challenging environmental stress factors for grassland ecosystems. We evaluated drought responses of beach cowpea (Vigna marina, Vm) using PEG6000 and found that Vm exhibits significantly greater drought tolerance than its close relative, cowpea (Vigna unguiculata, Vu). Vm's superior drought tolerance is linked to increased root activity, enhanced cellular homeostasis, higher osmolyte accumulation, and antioxidant enzyme activity. Additionally, the leaf system of Vm shows an unusual physiological response to drought, maintaining higher stomatal conductance and transpiration rates than Vu, which facilitates water transport and sustains leaf performance under stress. Root transcriptomes that underwent GO enrichment analysis showed significant enrichment genes related to cell wall composition and integrity in Vm, but not in Vu, suggesting a key difference in their drought response. By analyzing differentially expressed homolog genes (DEHGs) under drought conditions, we identified several drought-inducible marker genes including ABIG1, ANAC32, GA2OX1, CIPK15, PP2C49, and DRS1. These genes encode transcription factors, kinases, and antioxidant enzymes, with some involved in the ABA and GA signaling pathways, highlighting the complex mechanisms by which Vm adapts to drought stress. WGCNA identified 22 gene modules in Vm and 10 in Vu, each showing positive or negative associations with drought tolerance based on their correlation with physiological traits. Key DEHGs like LEA3, LOX4, SODC, and a cluster of XTH genes were found in these modules, highlighting distinct molecular responses to drought between the two species. This study uncovers key physiological and molecular mechanisms behind Vm's drought tolerance and provides valuable genetic resources for breeding drought-tolerant crops.